OPTIMIZING THE USE OF YOUTUBE CHANNEL TO IMPROVE STUDENTS’ SPEAKING ABILITY DURING ONLINE LEARNING - Despita Despita (Journal of English Education, Literature and Linguistics, 2021)
Technology plays an important role in people’s day-to-day life and can be used effectively for various aspects in education. The YouTube channel is regarded as one online material that can be integrated into traditional English lessons. It is also considered a source of online material that can play a vital role in the teaching and learning process. This study attempts to find the optimizing of YouTube channel to improve students’ speaking ability. A classroom action research was conducted to first semester college students of STIA Satya Negara Palembang. The population of this study was all of students in the first semester and the samples were 35 students in redundant class chosen using purposive sampling. The data were obtained from speaking assessment and interview and later analyzed by using constant comparative method and descriptive statistic. This study showed that YouTube channel as English learning material improved speaking ability of students including fluency, vocabulary, pronunciation, grammar, and content. Therefore, it can be concluded that optimizing of YouTube channel is able to improve the students’ speaking ability during online learning. Further study may concern on the optimizing of YouTube channel to teach other English ability like reading and writing. Keywords: YouTube Channel, Speaking Ability, Online Learning